A brief historical review of some selected negotiations procedures between the personnel committee of the Board of Education, La Crosse City Public School District No. 5, et al., and the bargaining committee of the La Crosse Education Association, 1963-1968 - Dyar, Harold (My University, 1968)
It was the purpose of this study (1) to outline briefly the history of some selected negotiations procedures between the Negotiating Committee of the La Crosse Education Association and the Personnel Committee of the Board of Education, La Crosse City Public School District No. 5, et al, 1963-1968, (2) to describe some of the problems relating to the procedures of negotiations, (3) to make recommendations for improving negotiation procedures. In investigating this problem, the minutes of meetings between 1963-1968 of the (1) Salary Committee, (2) the Classroom Teachers Negotiating Committee and the Personnel Committee of the Board of Education, and (3) the Executive Committee of the La Crosse Education Association were reviewed. This was followed by a study of the literature on teacher's salary negotiations obtained from (1) the Wisconsin Education Association, (2) the National Education Association, and (3) the American Federation of Teachers. A search for material related to the topic was conducted in the Wisconsin State University at La Crosse and La Crosse Public Libraries, and from the files of the La Crosse Tribune. There were some legal procedures, but not specific practices, that could be used to establish a set of rules for negotiations. There were too many differences in communities, leadership, and school board-teacher relationships which necessitate different practices in different local situations. At the date (July, 1968) of the conclusion of this paper, negotiations remained deadlocked between the board of education and the education association of the city of La Crosse. Nevertheless, it was the opinion of the researcher, that the representatives of the two bodies made good progress in organizing and making their start in negotiations.
Keywords: La Crosse Area Public Schools, Joint District No. 5 (Wis.); Collective bargaining -- Teachers -- Wisconsin -- La Crosse; La Crosse (Wis.) -- Board of Education; La Crosse Education Association (Wis.)